(untitled) - Aslıhan ERMAN ASLANOĞLU; Ömer Kutlu (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
The aim of this study is to evaluate, through the use of rubric, the student’s presentational behaviours which is one of the ways of expression of their high level thinking. performance tasks and get prepared for it in terms of a presentation. The presentations were evaluated by the teacher and the students in class. Besides, each presentation was recorded in a camera and was displayed to the science teachers at school for their evaluations. At the end of the study, the contribution to education of evaluation by “rubric” was asked to the students and the teachers who took part in the research, via a questionnaire. According to the results of the analysis made, it has been determined that there was no significant difference between the mean of the scores given by the viewer students and the teachers on each of the three performance tasks and the avarage of the scores they have given on the entire performance tasks; and that there was a high coherence in the scores given for the presentations by the teachers; and that these points were considered to be consistent. Furthermore, a relationship at 0.72 level was found between the marks which the students who made presentations were given by the class teachers and the marks they took from the first semester science lesson; as well as a relationship at 0.49 level between the points the spectator students gave for the presentations and the first semester science lesson marks of the students who made presentations.The results of survey stated that the teachers and the students believe that the use of rubric brings contribution to education